Back Cover: Zirconium Oxide Supported Palladium Nanoparticles as a Highly Efficient Catalyst in the Hydrogenation–Amination of Levulinic Acid to Pyrrolidones (ChemCatChem 14/2017). Issue 14 (24th July 2017) - Zhang, Jian; Xie, Bin; Wang, Liang; Yi, Xianfeng; Wang, Chengtao; Wang, Guoxiong; Dai, Zhifeng; Zheng, Anmin; Xiao, Feng‐Shou
Abstract : The Cover illustrates the synergistic effect of Pd nanoparticles and Lewis acid sites facilitating the selective hydrogenation–amination of biomass‐derived levulinic acid to produce pyrrolidones.In their Full Paper, J. Zhang, B. Xie et al. demonstrate that ZrO2 ‐supported Pd nanoparticles are highly active, chemoselective and reusable catalysts for the hydrogenation–amination of levulinic acid with H2 and various amines under mild reaction conditions. The excellent catalytic performance is reasonably attributed to the ZrO2 support, which has strong Lewis acidity to enhance the hydrogenation–amination reaction and hinder side reactions. More information can be found in the Full Paper by J. Zhang, B. Xie et al. onpage 2661 in Issue 14, 2017 (DOI:10.1002/cctc.201600739 ).